Itinerários geográficos: pensando e refletindo - Vasconcellos, Luiz Gonzaga Falcão (2014)
This study, entitled \"Geographic Itineraries: Think and Reflect\", aims to analyze and discuss the work of Urbanist geographer, and University Teacher, Luiz Gonzaga Falcão Vasconcellos, enjoying his contributions to Geography, considering the interrelationships of this with education, location and the city (urban); the research considered also the knowledge of connection between areas of knowledge, the university and the \"community.\" Specifically, the study aimed to analyze some work to think and reflect. Methodologically, the research developed with a view to analyze and discuss effected work and its contributions to the Geography themes and related areas. Rescue professionals and socio-cultural itineraries of a person does not mean focusing on this person, but to discuss and reflect about the trajectories, achievements and productions related to geography and its interrelations. In addition, you cannot separate the person and the teacher (geographer), since the teacher is a significant content of the person. Therefore, first, I revisited projects and other work done in the last 20 years. After this first stage, I selected some productions for consideration, as follows: Place and Urban Education; Popular Education: The City and the City; City, Urban, Public Health and Education; Urban Drawing Workshop: Children, Youth and the City, The city study and the city through music, poetry and poem: subsidies for primary and secondary education, Actions 14 - Right to the City: dialogue and brooding - university and popular communities in Uberlandia, and University and City: Convergences in Building a Participatory Urban Management(Participative Master Plan of Nova Ponte - MG). With the possible distance (at least the chronological distance), perform this route from my personal and professional experiences (important as a component of my continuing education as a geographer/teacher) is like writing chapters of an \"autobiography\" looking \"perceive myself\" in view of the endless improvement that can be experienced, if available for this. Thus, this research is divided into five chapters, namely: 1, Geography, City-Urban and Education; 2, What we have, and What we want: \"Drawing\" and Educating and Building \"Places\"; 3, Planning and Municipal Management: Participation and Citizenship; 4, City(ies), Cities in the City: Stages, Scenarios, Narratives ...and 5, Knowledge Connections: interdisciplinarities. As results, I understand that walk the paths of this research, give so many steps, review the route with different eyes and baggage from past achievements, was a journey that helped confirm the modest (but persistent) collaboration with the Education for Citizenship through the practices of Geography and socially referenced Education. An Education understood as that focused on emancipation and liberation of the historical and geographical subjects inserted in Brazilian society, which has generated for centuries an exclusive inclusion of large parts of its population. This is the reality on which I have proposed to learn and teach, thinking, reflecting and discussing ways and alternatives to overcome such situation, acting in the direction of Popular Education. This option assumed in the context of public higher education started more than 36 years, since when I searched professionally understand the social function of the university in external communities, especially the popular communities in order to connect knowledge and contribute to the prospect of rising levels of social inclusion.